(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2025)
A field trial was carried to explore the effect of GA3 (foliar, seed soaking or both) on growth, yield and photosynthetic pigments content of BARI Mung-6. The trial comprised of ten treatments viz. T0 = Control (Distilled water), T1, T2 and T3 = seed soaking with 25, 50 and 100 ppm GA₃ respectively; T4, T5 and T6 = foliar spray of 25, 50 and 100 ppm GA₃ respectively; T7 = 12.5 ppm GA₃ as seed soaking + 12.5 ppm GA₃ as foliar spray, T8 = 25 ppm GA₃ as seed soaking + 25 ppm GA₃ as foliar spray and T9 = 50 ppm GA₃ as seed soaking + 50 ppm GA₃ as foliar spray. Results revealed that foliar spray of 50 ppm GA₃ produced significantly taller plant (48.0 cm) than all other treatments although statistically identical to 25 ppm foliar treatment. The maximum number of branches (5.17) and leaves per plant (17.33), highest dry weight of leaves (0.73 g) and roots were noted from 25 ppm foliar application. Foliar application of 25 ppm GA3 also produced higher shoot-root ratio, biomass duration, absolute growth rate and relative growth rate than control. Outcome indicated that the highest number of pods per plant (5.50), longest pod (8.01cm), highest fresh (3.60 g) and dry weight (2.99 g) of pods, maximum number of seeds per plant (49.00), 1000-seed weight (47.72 g), yield per plant (2.34 g), yield per hectare (0.78 ton) and harvest index (62.46%) were obtained from 25 ppm foliar GA3 treatment. Increase in yield per plant due to foliar application of 25 ppm GA3 was 42.88% higher than control followed by seed soaking with 50 ppm (18.29%), 50 ppm foliar + 50 ppm seed soaking (13.42%) and seed soaking with 25 ppm (10.37%) treatments, respectively. Pigments content of leaves was remarkably influenced by GA3 treatments but varies depending on the methods application, concentration and plant growth. Out of ten treatments, foliar spray of 25 ppm GA3 produced better stimulation. J. Asiat. Soc. Bangladesh, Sci. 50(1-2): 113-123, June-December 2024